2014
DOI: 10.1016/j.chemosphere.2014.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic hazard and biodegradability of light and middle atmospheric distillate petroleum streams

Abstract: Light and middle atmospheric distillate petroleum substances are blended to produce fuels used in transportation and heating. These substances represent the majority by volume of crude oil refined products in the United States. The goal of this research was to develop biodegradability and aquatic toxicity data for four substances; heavy, straight-run naphtha (HSRN), hydro-desulfurized kerosene (HDK), hydro-cracked gas oil (HCGO), and catalytic-cracked gas oil (CCGO). Ready biodegradability tests demonstrated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Only acute toxicity tests are required for listing under the National Contingency Plan, but of course chronic effects are also a real concern. As expected, the longer exposure required to see chronic effects allows lower concentrations of hydrocarbons to exert an effect, and typical acute-to-chronic ratios are 1:10, that is, it may only take 10% of the acute LC 50 to have a chronic EC 50 . Again, these concentrations are for prolonged exposures, and it is not clear how these relate to the very low concentrations of dispersed oil that are found several days after dispersion …”
Section: Dispersantsmentioning
confidence: 94%
“…Only acute toxicity tests are required for listing under the National Contingency Plan, but of course chronic effects are also a real concern. As expected, the longer exposure required to see chronic effects allows lower concentrations of hydrocarbons to exert an effect, and typical acute-to-chronic ratios are 1:10, that is, it may only take 10% of the acute LC 50 to have a chronic EC 50 . Again, these concentrations are for prolonged exposures, and it is not clear how these relate to the very low concentrations of dispersed oil that are found several days after dispersion …”
Section: Dispersantsmentioning
confidence: 94%
“…The Joint Group of Experts on the Scientific Aspects of Marine Environmental Protection (1993) stated that a level of oil and grease as low as 0.01 mg L −1 in marine water would be necessary for protection of the biota. Based on toxicity tests with algae, cladocerans, and fish, Swigert et al (2014) observed that chronic no-observed-effect loading rates ranged between 0.05 and 0.64 mg L −1 . Carls and Meador (2009), in a review on the toxicity of petrogenic PAHs to fish embryos, stated that the toxic threshold should be 0.5 µg L −1 or lower.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies argued the pass levels for readily biodegradability and agreed that the 10-day time window criterion is justified and useful (Mei et al 2015;Pedrazzani et al 2012;Reuschenbach et al 2003;Swigert et al 2014). Figure 6 shows the degradation rate of DDA and sodium oleate and the start time of the 10-day window, if present.…”
Section: Analysis Of Samples From the Co 2 Headspace Testmentioning
confidence: 95%